Voluntary school fees in segregated public schools: how selective public schools turbo-charge inequity and funding gaps. Issue 1 (2nd January 2022) - Rowe, Emma; Perry, Laura B.
ABSTRACT: Parent-generated revenue in public schools, in the form of fee-giving or fundraising, is fast developing as a robust source of financial revenue for public schools in OECD countries. In this paper we draw on a comprehensive empirical dataset of parent-generated financial revenue for public schools located in New South Wales, Australia. We draw on a census dataset of all public schools over a five-year period, examining how funding gaps are exacerbated by selective processes and school segregation . The analysis compares parent-generated financial revenue within two types of public schools, namely select-entry public schools and local comprehensive public schools. We find that select-entry public schools consistently generate more than three-times more income across different measures, and over a five-year period. Furthermore, the amount of revenue for select-entry schools annually grows, and the gap increases, suggesting that as market logics intensify, cyclical disadvantage and residualisation of comprehensive public schools increase.